The Impact of physical activity on gastrointestinal health and prevention and treatment of common gastrointestinal diseases: Irritable Bowel Syndrome and Inflammatory Bowel Diseases - Mąsior, Magdalena Natalia; Kapler, Marta; Kotuła, Jacek; Zinkow, Karolina (Quality in Sport, 2024)
Irritable Bowel Syndrome (IBS) and Inflammatory Bowel Diseases (IBD), among them Crohn’s disease and ulcerative colitis, are common chronic diseases affecting a growing group of patients. Physical activity (PA) is an important part of a healthy lifestyle. The aim of the study was to critically evaluate current knowledge of impact of PA on gastrointestinal (GI) health and prevention and treatment of some most common GI tract diseases, such as IBS and IBD. The comprehensive research of literature available on PubMed, Google Scholar, ResearchGate and Springer Link was performed. PA improves function of GI by increasing colon transit and bowel movements. These mechanisms contribute to reducing the risk of colorectal cancer and, to varying degrees depending on location, other digestive-system cancers. There is a potential association between PA and the more health-beneficial gut microbiota, but more research in this area is needed. Sedentary lifestyle seems to be a risk factor for IBD, while physical activity seems to be a protective factor only for Crohn disease. Altough, PA contributes to improvement of quality of life and reduction of stress in patients with IBD, futher conclusions on the effect of PA on the course of ulcerative colitis and Crohn disease still require expanded research. Available literature suggests that physical activity prevents obesity, a proven risk factor for worsening the course of the disease, and osteoporosis, an important complication of glucocorticosteroid therapy. Despite evidence of a sedentary lifestyle as a risk factor for IBS, there is still a lack of studies examining the impact of physical activity as a protective factor. the number of RCTs examining the effect of PA on the course of IBS remains insufficient, and studies conducted should take into account the various symptoms of IBS.